Kitab Kuning and Religious Moderation: A Study on State Islamic Universities in Indonesia - Nasution, Sahkholid; Asari, Hasan; Al-Rasyid, Harun (Journal of Al-Tamaddun, 2024)
Indonesia is a multi-religious country that is constantly seeking ways to promote religious moderation. One of the recently adopted strategies is to empower Kitab Kuning, which are the classical source books used in pesantren (Islamic boarding schools), at Maʻhad al-Jāmiʻah of State Islamic Universities. The objective of this study is to provide qualitative-descriptive analyses of the contents of Kitab Kuning related to religious moderation, the teaching methods of Kitab Kuning, and the extent to which moderation is practiced in Maʻhad’s daily life. The data for the study were obtained through in-depth interviews, focus group discussions, site observations, and content analyses of related documents. The participants were heads of Maʻhad al-Jāmiʻah, instructors, students, and administrators. The data was processed using the procedures suggested by Miles and Huberman. The findings indicate that Maʻhad al-Jāmiʻah intentionally uses Kitab Kuning to propagate basic values of Islam Wasatiyah, such as love, respect, balance, modesty, justice, and fairness. The teaching strategies adopted at Maʻhad are based on pesantren’s tradition with a focus on contextualization, which enables the moderation values to be implemented in students’ daily lives. These values have played a vital role in maintaining healthy relations between students from different cultural and religious backgrounds. Therefore, Kitab Kuning should be seen as an alternative strategy to ensure Islam Wasatiyah in Indonesia. The fact that the learners are university students is significant, as they can propagate moderation into the wider society once they graduate.